2015
DOI: 10.1183/13993003.00665-2015
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D represses rhinovirus replication in cystic fibrosis cells by inducing LL-37

Abstract: Vitamin D has immunomodulatory properties in the defence against pathogens. Its insufficiency is a widespread feature of cystic fibrosis (CF) patients, which are repeatedly suffering from rhinovirus (RV)-induced pulmonary exacerbations.To investigate whether vitamin D has antiviral activity, primary bronchial epithelial cells from CF children were pre-treated with vitamin D and infected with RV16. Antiviral and anti-inflammatory activity of vitamin D was assessed. RV and LL-37 levels were measured in bronchoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 46 publications
3
54
1
2
Order By: Relevance
“…The ability of LL-37 to directly inhibit a number of viruses has been reviewed previously (Barlow et al, 2014b), with further activities found against Aichi virus A (Vilas Boas et al, 2017), human adenoviruses 8 and 19 (HAdV-8 and HAdV-19) (Gordon et al, 2005; Uchio et al, 2013), hepatitis C virus (HCV) (Matsumura et al, 2016), human papillomavirus 16 (HPV16) (Buck et al, 2006), human rhinovirus (HRV) (Findlay et al, 2017; Schögler et al, 2016; Sousa et al, 2017), and varicella zoster virus (VZV) (Crack et al, 2012). While LL-37 has only been measured at 0.5 μg/ml in saliva (Bachrach et al, 2006; Takeuchi et al, 2012) and 10 μg/ml in gingival crevicular fluid 29 , the actual physiological concentration may be much higher at sites closer to the oral epithelial cells themselves due to the diffusion of the peptides once released from cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of LL-37 to directly inhibit a number of viruses has been reviewed previously (Barlow et al, 2014b), with further activities found against Aichi virus A (Vilas Boas et al, 2017), human adenoviruses 8 and 19 (HAdV-8 and HAdV-19) (Gordon et al, 2005; Uchio et al, 2013), hepatitis C virus (HCV) (Matsumura et al, 2016), human papillomavirus 16 (HPV16) (Buck et al, 2006), human rhinovirus (HRV) (Findlay et al, 2017; Schögler et al, 2016; Sousa et al, 2017), and varicella zoster virus (VZV) (Crack et al, 2012). While LL-37 has only been measured at 0.5 μg/ml in saliva (Bachrach et al, 2006; Takeuchi et al, 2012) and 10 μg/ml in gingival crevicular fluid 29 , the actual physiological concentration may be much higher at sites closer to the oral epithelial cells themselves due to the diffusion of the peptides once released from cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in CF respiratory cell lines showed anti-inflammatory and anti-bacterial effects after treatment with 1,25(OH) 2 D in response to bacterial stimuli [64,65]. Furthermore, it was demonstrated that vitamin D increased the mRNA expression of cathelicidin from primary bronchial epithelial cells collected from CF patients with no evidence for an antiviral response following a rhinoviral infection [42]. Even though mechanistic studies mostly were done in vitro, few studies in human suggest that the positive effects of vitamin D on exacerbations in CF are mostly attributed to its immunomodulatory properties as reflected by reduced serum IL-6, TNF levels [61], and IL-8 levels [66] or reduced serum Ig(G) levels [45].…”
Section: Vitamin D In Cystic Fibrosismentioning
confidence: 94%
“…Also genetic studies confirm that polymorphism in the VDR independently associates with susceptibility to URI. Finally, in vitro studies in epithelial cell lines [40] and in human primary bronchial epithelial cells [41,42] infected with rhinoviruses show that vitamin D is able to increase the antiviral defenses most likely via an upregulation of cathelicidin. From a mechanistic point of view, it is clear that vitamin D can be an important modulator of the host defense against respiratory infections by potentiating the clearance of pathogens while attenuating the associated inflammatory burst.…”
Section: Vitamin D To Prevent or Treat Exacerbationsmentioning
confidence: 99%
“…The potential anti‐viral effect of such antimicrobial peptides has recently gained attention in the field of virology. Indeed, the potent anti‐viral activity of cathelicidin was demonstrated against several viral infections including HIV‐1, vaccinia virus, HSV‐1/2, influenza, rhinovirus (RV), and HCV …”
Section: Introductionmentioning
confidence: 99%
“…49 Furthermore, LL37 can promote the clearance of respiratory pathogens by inducing apoptosis of infected epithelial cells through enhanced mitochondrial membrane depolarization and release of cytochrome c. 50The potential anti-viral effect of such antimicrobial peptides has recently gained attention in the field of virology. Indeed, the potent anti-viral activity of cathelicidin was demonstrated against several viral infections including HIV-1, 51 vaccinia virus,52 HSV-1/2,53,54 influenza, 55 rhinovirus (RV),56,57 and HCV 58,59. LL37 inhibits viral infection by blocking either viral entry into host cells or suppressing virus activity.…”
mentioning
confidence: 99%